Pemikiran Dakwah Endang Saefudin Anshori - Hajir Tajiri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2016)
As part of Islamic activities, dakwah will always be studied and developed by Muslim thinkers. A row of figures has been contributing his thoughts about da'wah, including Endang Saefudin Anshori (ESA). The person has long passed away but his writing became a legacy of thought that helped raise the thinking of Islamic da'wah. This research will reveal about ESA da'wah thought in the book entitled “Wawasan Islam Pokok-pokok Pikiran tentang Islam dan Umatnya” by paying attention to important themes of da'wah namely: da'wah concept, elements and problematika da'wah. The research method uses content analysis and comparing ESA thinking, the reality of life and the views of other preachers of dakwah. The results showed that the pattern of da'wah thought Endang Saefudin Anshori still feels the impression of a great struggle between the ideology that developed in the world. By understanding the thought of ESA is understood da'wah as an effort to translate Islam in various aspects of life.